A Study on Light Weight Cryptography Algorithms for Data Security in IOT - Sri Lakshmi, M; Srikanth, V (International Journal of Engineering and Technology, 2018)
IOT - things like the smart devices and sensors that connects and communicates through Internet. IOT applications like smart home, smart vehicles, smart retail, which makes the mankindâ€™s life easier.Â There is a prediction that we will be having million of devices connects to the Internet. Since the sensitive devices like baby monitoring devices,Â health monitoring devices are the part of interconnected world there is the necessity to address the consequence of the security aspects of the IOT. The built-in nature of the IOT is to trace userâ€™s identity easily, so the security and privacy concerns like stealing the data, disruption of operations and even the loss of life are becoming critical issues in todayâ€™s IOT applications.Â Due to the resource constrained environment in IOTÂ the conventional algorithms is not enough to ensure the data security. So we need a less computational cost in terms of power consumption and memory management and more efficient cryptography algorithms which are discussed in this paper.Â Â